Ethanolic leaf extract of Irvingia gabonensis (o’Rorke) Baill protects against nephrotoxocity and hepatotoxicity in cadmium-induced wistar albino rats - Ewere, Efosa; Oyebadejo, Samson; Peter, Victor (International Journal of Pharmacology and Toxicology, 2016)
Cadmium is a well-known environmental pollutant that has been proven to be nephrotoxic and hepatotoxic in the body. In this study, the effect of ethanolic leaf extract of Irvingia gabonensis (O’Rorke) Baill (IG) against cadmium-induced nephrotoxicity and hepatotoxicity in Wistar albino rats was investigated. 30 female wistar rats of weights between 98-153g were grouped into 6 groups of 5 animals each. Group 1 served as the control and was placed on rat feed and water. Groups 2, 3, and 4 were administered 10mg/Kg body weight (mg/kgbw) of cadmium chloride (CdCl2) only,10mg/Kgbw CdCl2 and 200mg/kgbw extract, 10mg/Kgbw CdCl2 and 400mg/kgbw extract, respectively. Groups 5 and 6 were given 200mg/kgbw and 400mg/kgbw of IG extract respectively and the treatments lasted for 28 days. Results obtained revealed significant (p<0.05) increases in the serum levels of all renal and liver function biomarkers in group 2 (CdCl2 only) as compared with the control. There were however significant (p<0.05) decreases in the serum levels of the assayed parameters when groups 3 and 4 were respectively compared with group 2. It can therefore be concluded that ethanolic leaf extract of Irvingia gabonensis (O’Rorke) Baill enhances the integrity of the kidneys and liver of cadmium-induced wistar albino rats.